Synthesis and Structure of Hetaryl Substituted 2,5-dioxo-1,2,3,4,5,6,7,8-Octahydroquinolines - Ozokan, Kadri G.; Kaban, Seniz (Current Organic Synthesis, 2022)
Aims and Objective: Condensation of 5-hetarylidene-2,2-dimethyl-1,3-dioxane-4,6- diones with 5,5-dimethyl-3-arylamino-2-cyclohexanones yields 1-aryl-4-hetaryl-7,7-dimethyl-2,5- dioxo-l,2,3,4,5,5,7,8-octahydro-quinolines. The structures of all the synthesized compounds have been verified by IR, 1H-NMR, 13C-NMR, and mass spectral methods. The 13C-NMR assignments were supported by HSQC and HMBC experiments. Moreover, spin decoupling and NOE experiments have been carried out in order to elucidate stereoisomeric configurations of the compounds. It has been established that the N-phenyl ring, which projects from the plane of the octahydroquinolinedione ring, has a shielding effect on the magnetic field of the protons at 7- and 8-positions of the ring in the molecules of the compounds synthesized. Materials and Methods: The NMR spectra were recorded on a Varian Gemini spectrometer [400 MHz (1H) and 100 MHz (13C)]. EI mass spectra were obtained with a Hewlett Packard GC/MS 6890/5973 machine. MALDI-TOF mass measurements were recorded on a Bruker auto-flex III smart beam. Results: Various reaction conditions were applied in order to find an optimum and convenient procedure for the formation of octahydroquinoline derivates having hetaryl group. The highest yields (40-50 %) were achieved using acetic acid as solvent, p-toluenesulphonic acid as acidic catalyst, and excess enaminone (1.5 equiv). Conclusion: We synthesized eight new 1-aryl-7,7-dimethyl-4-hetaryl-1,2,3,4,5,6,7,8-octahydroquinoline- 2,5-dione compounds containing thienyl core as a result of Michael addition reaction of Knoevenagel products of Meldrum’s acid with dimedone enaminone compounds. Optimum circumstances were established using various reaction conditions and catalyzers throughout the research. The structures of all the synthesized compounds were analyzed by IR, 1H-NMR, 13CNMR, and mass spectral methods. Furthermore, the structures were verified with the help of 2D (HSQC and HMBC), spin decoupling, and NOE NMR techniques.
Keywords: enaminone